2019
DOI: 10.1371/journal.pone.0215298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the minimum region of flatfish myostatin propeptide (Pep45-65) for myostatin inhibition and its potential to enhance muscle growth and performance in animals

Abstract: Myostatin (MSTN) negatively regulates skeletal muscle growth, and its activity is inhibited by the binding of MSTN propeptide (MSTNpro), the N-terminal domain of proMSTN that is proteolytically cleaved from the proMSTN. Partial sequences from the N-terminal side of MSTNpro have shown to be sufficient to inhibit MSTN activity. In this study, to determine the minimum size of flatfish MSTNpro for MSTN inhibition, various truncated forms of flatfish MSTNpro with N-terminal maltose binding protein (MBP) fusion were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The free fatty acid concentration in serum was tended to decrease by the administration of CSE, indicating an active utilization of blood free fatty acids by CSE administration. This result is in agreement with other studies that also reported a decrease in blood free fatty acid level by the administration of MSTN-inhibitory compounds in mice fed either a regular [ 32 ] or high-fat diet [ 33 ]. However, the levels of blood glucose and triglyceride were not affected by the administration of CSE in contrast to the results of the above reports [ 17 , 31 ], where decreases in blood glucose and triglyceride were observed by MSTN-inhibitory compound administration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The free fatty acid concentration in serum was tended to decrease by the administration of CSE, indicating an active utilization of blood free fatty acids by CSE administration. This result is in agreement with other studies that also reported a decrease in blood free fatty acid level by the administration of MSTN-inhibitory compounds in mice fed either a regular [ 32 ] or high-fat diet [ 33 ]. However, the levels of blood glucose and triglyceride were not affected by the administration of CSE in contrast to the results of the above reports [ 17 , 31 ], where decreases in blood glucose and triglyceride were observed by MSTN-inhibitory compound administration.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of the coffee silverskin ethanol extracts (CSE; mixture of various varieties) on MSTN-, GDF11-, and Activin A-induced Smad3 phosphorylation were examined by the Western blot analysis following the procedure previously described [ 32 ]. HepG2 cells were seeded in 6-well plates at 2 × 10 5 cells per well and grown in DMEM containing 10% FBS and 1% penicillin/streptomycin at 37 °C with 5% CO 2 for 24 h. Cells were then switched to serum-free DMEM for 4 h, followed by treatment with 10-nM MSTN (R&D Systems, Minneapolis, MN, USA), 10-nM MSTN plus CSE (50 µg/mL), 10-nM GDF11 (R&D Systems, Minneapolis, MN, USA), 10-nM GDF11 plus CSE (50 µg /mL), 10-nM Activin A (R&D Systems, Minneapolis, MN, USA), and 10-nM Activin A plus CSE (50 µg /mL) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…A pluripotent cell line C3H10T1/2 can be induced by the glucocorticoid dexamethasone to form adipocytes, and this process can be reinstated by replacing dexamethasone with recombinant MSTN 13 . In comparison, adipogenesis was not induced by the treatment with MSTN in 3T3-L1 cells, which is an adipocyte lineage-committed cell line believed to be further differentiated than C3H10T1/2 cells 4,14,15 . A possible explanation is that MSTN activates SMAD4 to enhance miR124-3p to repress glucocorticoid receptor, resulting in the inhibition of adipogenic differentiation of 3T3-L1 cells 16 .…”
Section: Discussionmentioning
confidence: 89%
“…Functional blockade of MSTN results in the double muscling trait in animals, which features overgrown skeletal muscle and reduced fat mass. Owning to this advantage, MSTN has been a prime genetic target for the development of high-leanness animal cultivars in livestock, poultry and fishery industries, via multifaceted approaches like ectopically expressed MSTN propeptide, dominant negative competitor, RNA interference, gene targeting and gene editing [1][2][3][4] . Among these methods, programmable nuclease-mediated gene editing proved to be robust to introduce random indels into the coding sequence of MSTN, thus disrupting its frame readability.…”
mentioning
confidence: 99%
“…In addition to myod2 and mymk , the inclusion of antioxidants also modified the expression of mstn1 in postlarvae. In mammals, mstn gene is known to act as potent regulator of muscle growth, and a mstn -knockout fish highly increased muscle mass ( de Santis et al, 2012 ; Kim J. et al, 2019 ; Kim J. H. et al, 2019 ). Contrarily to mammals, mstn transcription in fish species is ubiquitous expressed indicating an involvement in other physiological mechanisms as well as in skeletal muscle growth regulation ( Campos et al, 2010 ; Li et al, 2012 ; Canada et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%